Wpływ wilgotności względnej powietrza na występowanie pożarów w lasach w centralnej Polsce - Konca-Kędzierska, Krystyna; Pianko-Kluczyńska, Krystyna (Leśne Prace Badawcze, 2018)
The purpose of the present work was to answer the question of how and to what extent information about low air humidity in a selected area can be used in determining the fire risk. The central region as defined in the Classification of Territorial Units for Statistics (NUTS) was selected for the study, because this classification is also used in the National Fire Information System, which provides data on the number of forest fires. Data on humidity for a given region was taken from the synoptic or climatic station of The Institute of Meteorology and Water Management – National Research Institute (IMGW-PIB) located in the region. Two independent experiments were conducted based on various methodological assumptions. In experiment A, the main Focus was on humidity deficit, as defined by nine different indicators. Using the relative risk and the Jaccard index, their connection to fire cases of third class or higher was studied. A class reconstruction of the number of fires was also carried out using the fuzzy analogues method and the obtained reconstructions were evaluated using cross-correlation indicators in contingency tables. In experiment B, correlation relationships between the number of fires and the annual characteristics of relative humidity were studied. In order to use the association measures in the cross-tabulation tables, the number of fires and humidity characteristics were categorised using quantiles. The relationship between the number of fires and the percentage share of low-humidity (